The Application of Metaphor Identification Procedure (Mip) And Conceptual Metaphor In Japanese Poetry - Pariasa, I Gede; Rajeg, I Made; Sosiowati, I Gusti Ayu Gede (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 24 No 2 (2017): September, 2017)
The aims of this study are to apply the method of the metaphor identification procedure (Pragglejaz Group, 2007) to find out the linguistic metaphors in Japanese poetry, and apply the theory of conceptual metaphor (CMT) (Lakoff & Johnson, 2003) to find out the conceptual metaphors that motivate the use of linguistic metaphor in the poetry. Descriptive qualitative method was applied in this research. The data of this research were taken from Takuboku Ishikawa dan Segenggam Pasir  book, written by Edizal (2000). The result shows that metaphor identification procedure (MIP) provides a explicit, reliable, and flexible instrument for identifying linguistic metaphors and conceptual metaphor theory (CMT) provides a systematic tool to identify the concepts behind the linguistic metaphors. The linguistic metaphors identified in the poetry are: koi no amasa to nagashisa, kanashimi no tama, and te ga shirokukatsu dainariki . The conceptual metaphors that are found to underlie the linguistic metaphors are:  VIRTUE IS WHITE, LOVE IS FOOD OR DRINK, SAD IS INSTABILITY